Impairment Mechanisms and Intervention Approaches for Aged Human Neuromuscular Junctions - Badawi, Yomna; Nishimune, Hiroshi (Frontiers in Molecular Neuroscience, 2020)
The neuromuscular junction (NMJ) is a chemical synapse formed between a presynaptic motor neuron and a postsynaptic muscle cell. NMJs in most vertebrate species share many essential features; however, some differences distinguish human NMJs from others. This review will describe the pre- and postsynaptic structures of human NMJs and compare them to NMJs of laboratory animals. We will focus on age-dependent declines in function and changes in the structure of human NMJs. Furthermore, we will describe insights into the aging process revealed from mouse models of accelerated aging. In addition, we will compare aging phenotypes to other human pathologies that cause impairments of pre- and postsynaptic structures at NMJs. Finally, we will discuss potential intervention approaches for attenuating age-related NMJ dysfunction and sarcopenia in humans.